Giving Processed Gonad of Sea Urchins and Skipjack Fish (Katsuwonus pelamis) to Stunted Children: Acceptability and Effectiveness - Hariani, Hariani; Fathurrahman, Teguh; Wiralis, Wiralis; Astuti, Trina; Imanuddin, Imanuddin (YCAB Publisher, 2025)
Background:Stuntingis a critical chronic nutritional issue prevalent in developing countries, including Indonesia, with profound effects on children's physical growth, cognitive development, and future productivity. Objective: This study aims to assess the acceptability of nuggets formulated from sea urchin gonads (Diadema setosum) and skipjack fish (Katsuwonus pelamis) as a nutritional supplement for addressing stunting in children under five years of age. Methods: A quantitative descriptive approach was employed, utilizing organoleptic testing. The study involved 161 panelists comprising nutrition students and mothers of toddlers attending the Posyanduin Soropia District, Konawe Regency. Results: The organoleptic test results indicated that the nuggets were well-accepted in terms of color, aroma, taste, and texture. A majority of the panelists rated them as